Advances in Experimental Design: Applications in Behavioral Research - Dhanusha. C (AG Volumes, 2024)
The purpose of this review paper is to look into the purpose of experimental research in the understanding of behaviour research. It analyses the experimental design as well as different kinds of experimental research designs, emphasising recent development that improve analytical precision and methodological rigour. The paper highlights the applicability of experimental design in the field of human behaviour by examining the applications used to study it, while also emphasising behavioural research. The paper illustrates the invaluable contributions that experimental research continues to make to our understanding of human behaviour, thereby promoting evidence-based practices in a variety of fields.